2007
DOI: 10.1055/s-2007-990241
|View full text |Cite
|
Sign up to set email alerts
|

An Algal-Derived DL-Galactan Hybrid is an Efficient Preventing Agent for in vitro Dengue Virus Infection

Abstract: The DL-galactan hybrid C2S-3, isolated from the red seaweed Cryptonemia crenulata (Halymeniaceae, Halymeniales), is a potent and selective inhibitor of the multiplication of diverse strains of DENV-2 in Vero cells with higher effectiveness than the reference polysaccharide heparin. The presence of the compound either only at virus adsorption or at virus internalization exerted a significant and dose-dependent inhibition in DENV-2 plaque number. The compound failed to inactivate DENV-2 directly by incubation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 16 publications
2
37
0
1
Order By: Relevance
“…our results agree with other studies testing distinct natural products against DENV. Carbohydrate-binding agents originated from plant lectins can affect the binding of the virus to cell and subsequently inhibit viral replication (Talarico et al 2007, Alen et al 2009). Inhibitory activities by both extract and alkaloidal fraction of Uncaria tomentosa on infection rates and cytokine levels in treated monocytes-DENV infected have been reported (Reis et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…our results agree with other studies testing distinct natural products against DENV. Carbohydrate-binding agents originated from plant lectins can affect the binding of the virus to cell and subsequently inhibit viral replication (Talarico et al 2007, Alen et al 2009). Inhibitory activities by both extract and alkaloidal fraction of Uncaria tomentosa on infection rates and cytokine levels in treated monocytes-DENV infected have been reported (Reis et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Charged polyanions such as heparin and other sulfated polysaccharides act as HS-mimicking molecules and interfere with E protein-HS DIII target peptides Impairment of virus cell recognition [107] DIII target mAbs Impairment of virus cell recognition [25,108,109] CBAs: lectins HHA, GNA and UDA Impairment of virus cell recognition [111,112] Glycomimetic DC-SIGN ligands Impairment of virus cell recognition [113] Teicoplanin aglycon analog: LCTA-949 Impairment of virus cell recognition and probable of other entry stage [115] Sulfated galactans Inhibition of virus adsorption and penetration [46,117,118,120] Fucoidans Inhibition of virus adsorption and penetration [119,120] …”
Section: • • Inhibitors Of Virus Adsorption and Penetration Sulfated Pomentioning
confidence: 99%
“…A great variety of polysaccharides such as DL-galactan hybrids, fucoidans and carrageenans, obtained from marine algae, display anti-DENV-2 activity [20,46,[117][118][119]. It has been demonstrated that whereas DENV-2 was the most susceptible serotype to carrageenan G3d and DL-galactan hybrid C2S-3, DENV-1 was resistant to both polysaccharides.…”
Section: Carrageenans Inhibition Of Virus Adsorption and Penetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated activity of several species of algae against HIV-1 [1,2], HSV-1 [3][4][5][6], HSV-2 [4,5] and dengue type 2 strains [7]. Thus, marine algae provide a rich source for the discovery of antiviral drugs.…”
Section: Introductionmentioning
confidence: 99%